2019
DOI: 10.1016/j.jsbmb.2018.09.013
|View full text |Cite
|
Sign up to set email alerts
|

GPER and ERα mediate estradiol enhancement of mitochondrial function in inflamed adipocytes through a PKA dependent mechanism

Abstract: Please cite this article as: Bauzá-Thorbrügge M, Rodríguez-Cuenca S, Vidal-Puig A, Galmés-Pascual BM, Sbert-Roig M, Gianotti M, Lladó I, Proenza AM, GPER and ER␣ mediate estradiol enhancement of mitochondrial function in inflamed adipocytes through a PKA dependent mechanism, Journal of Steroid Biochemistry and Molecular Biology (2018), https://doi.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 83 publications
(91 reference statements)
1
11
0
Order By: Relevance
“…2014;Sbert-Roig et al, 2016;Galmes-Pascual et al, 2017;Bauzá-Thorbrügge et al, 2019). This effect was observed here, as increases in mitochondrial footprint, under most experimental conditions.…”
supporting
confidence: 70%
“…2014;Sbert-Roig et al, 2016;Galmes-Pascual et al, 2017;Bauzá-Thorbrügge et al, 2019). This effect was observed here, as increases in mitochondrial footprint, under most experimental conditions.…”
supporting
confidence: 70%
“…Remarkably, iron treatment combined with ovariectomy prevented training‐induced increases in CREB phosphorylation, whereas G1 administered immediately after training was able to restore CREB phosphorylation in the iron‐OVX group, similar to the recovery of memory deficits in this group (Experiments 2 and 3). Although the stimulation of GPER has not been previously linked to the cAMP/PKA/CREB pathway in the CNS, a recent study demonstrated that PKA inhibition prevented the improving effects of G1 on mitochondrial function in adipocytes under inflammatory conditions . CREB is a transcription factor that, when phosphorylated, regulates the expression of genes critically involved in synaptic plasticity and long‐term memory consolidation .…”
Section: Discussionmentioning
confidence: 99%
“…or vehicle (Veh) was administered 15 min before training and G1 (10 μg kg -1 , s.c.) dissolved in sunflower seed oil (Veh) was administered immediately after training of OP or IA (n = 8-9 per group in OP and n = 8-10 per group in IA). A significant difference between Iron-OVX-Veh-G1 compared to Iron-OVX-Veh-Veh is indicated as (**P < .0001), as well as between Iron-OVX-Veh-G1 compared to Iron-OVX-H89-G1 ( ## P < .0001 or # P < .05) 49 CREB is a transcription factor that, when phosphorylated, regulates the expression of genes critically involved in synaptic plasticity and long-term memory consolidation. [50][51][52][53][54] We have previously demonstrated that acute administration of rolipram, an agent that enhances the cAMP/PKA/CREB signalling pathway via the inhibition of phosphodiesterase type 4 (an enzyme that catalyses hydrolysis of cAMP), improves iron-induced memory deficits in male rats.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, treatment of DIO mice with E2 increased lipid oxidation to reduce obesity ( D’Eon et al, 2005 ). Cell-based studies revealed that in 3T3-L1 adipocytes treated with IL6 to induce inflammation-mediated mitochondrial dysfunction, treatment with E2 or G-1 attenuated the adverse effects of inflammation on mitochondrial function through activation of protein kinase A by ER α and GPER, thereby increasing mitochondrial biogenesis and oxygen consumption ( Bauza-Thorbrugge et al, 2019 ). Interestingly, in another model of GPER KO mice, GPER-lacZ mice (mutant mouse that harbors a β -galactosidase (lacZ) reporter within the Gper locus, disrupting Gper expression), female but not male GPER KO mice exhibited increased lipid accumulation in the liver along with decreased circulating HDL levels compared to WT mice ( Meoli et al, 2014 ).…”
Section: Roles Of Gper In Obesity Fat Deposition and Energy Homeostasismentioning
confidence: 99%